Acupuncture combined with Chinese herbs versus Chinese herbs alone to improve the clinical efficacy of uterine fibroids: a systematic review and meta-analysis - Chen, Tianyu; Chen, Xin; He, Wei; Ma, Xiaojing; Zuo, Zheng (Frontiers in Oncology, 2024)
ObjectiveThe objective of this study was to evaluate the clinical efficacy of acupuncture combined with Chinese herbs versus Chinese herbs alone in treating uterine fibroids.MethodsA literature search of eight databases identified nine randomized controlled trials (RCTs) evaluating the clinical efficacy of acupuncture combined with Chinese herbs compared to Chinese herbs alone for treating uterine fibroids. Subsequently, data extraction and analysis were conducted to assess the methodological quality and risk of bias in the studies, followed by an analysis of the data from the randomized controlled trials.ResultsNine randomized controlled trials involving 640 women were included. The results indicated that acupuncture combined with Chinese herbs significantly increased the overall clinical efficacy rate [Z=5.00, P=0.74, relative risk(RR)1.20, 95%CI 1.12 to 1.30, P<0.00001, I²=0%] and reduced the size of uterine fibroids [Z=2.95, P=0.003, SMD=-0.82, 95%CI -1.36 to -0.27, P<0.00001, I²=90%].ConclusionsStudies have shown that acupuncture combined with Chinese herbs reduces uterine size, lowers hormone levels, and improves quality of life. According to the findings of this study, acupuncture combined with Chinese herbs has a more positive effect on the treatment of uterine fibroids than Chinese herbs alone. However, due to the limited number and quality of the included studies, these conclusions need to be validated by further high-quality research.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42024507248.